Critique & praxis a critical philosophy of illusions, values, and action - Harcourt, Bernard E. 1963- (Columbia University Press, 2020)
Critical philosophy has always questioned the division between theory and practice. At its best, it aims to turn contemplation into emancipation, seeking to transform society in pursuit of the flourishing of humanity. Yet today's critical theorists often seem to engage only in critique. These times of crises demand more. No philosophical school is better equipped to deal with the challenges of the present. But how can we rethink critique in order to redirect it outward toward changing the world? In Critique and Praxis, Bernard E. Harcourt challenges us to move beyond the complacency of decades of philosophical detours and to harness critical thought to the need for action. In a time of increasing awareness of economic and social inequality, of the privileges of some and the deprivations of the many, Harcourt calls on us to make society more equal and just. Only critical theory can guide us toward a more concerted and self-reflexive pursuit of justice. Charting a vision for political action and social transformation, Harcourt argues that instead of answering the question, "What is to be done?" we must now turn it back onto ourselves and ask, "What more am I to do?" Critique and Praxis advocates for a new path forward that constantly challenges each and every one of us to ask what more we can do to realize a society based on equality and justice. Joining his decades of activism, social-justice litigation, and political engagement with his career of critical theory and philosophical work, Harcourt has written a magnum opus
Keywords: Gerechtigkeit; Kritische Theorie; Critical theory; Political science / Philosophy; Political participation; Social action